Releasing the spindle assembly checkpoint without tension - McEwen, Bruce F. (The Rockefeller University Press, 2009)
Eukaryotic cells have evolved a spindle assembly checkpoint (SAC) that facilitates accurate genomic segregation during mitosis by delaying anaphase onset in response to errors in kinetochore microtubule attachment. In contrast to the well-studied molecular mechanism by which the SAC blocks anaphase onset, the events triggering SAC release are poorly understood. Papers in this issue by Uchida et al. (Uchida, K.S.K., K. Takagaki, K. Kumada, Y. Hirayama, T. Noda, and T. Hirota. 2009. J. Cell Biol. 184:383–390) and Maresca and Salmon (Maresca, T.J., and E.D. Salmon. 2009. J. Cell Biol. 184:373–381) make an important advance by demonstrating that SAC release depends on molecular rearrangements within the kinetochore rather than tension-produced stretch between sister kinetochores.